Solubility Limits of Cholesterol, Lanosterol, Ergosterol, Stigmasterol, and β-Sitosterol in Electroformed Lipid Vesicles - Stevens, Mark M. (2010)
Here we use nuclear magnetic resonance to measure the solubility limit of several biologically relevant sterols in electroformed giant unilamellar vesicle membranes containing phosphatidylcholine (PC) lipids in ratios of 1:1:X DOPC:DPPC:sterol. We find solubility limits of cholesterol, lanosterol, ergosterol, stigmasterol, and β-sitosterol to be 65-70%, ~35%, 30-35%, 20-25%, and ~40%, respectively. The low solubilities of stigmasterol and β-sitosterol, which differ from cholesterol only in their alkyl tails, show that subtle differences in tail structure can strongly affect sterol solubility. Below the solubility limits, the fraction of sterol to PC-lipid in electroformed vesicles linearly reflects the fraction in the original stock solutions used in the electroformation process.